Satisfactory service beaviour based on clients and takaful agencies perspective: case study at academy etiqa takaful berhad in Kuala Lumpur / Siti Fatimah Husain Muhamad Husain - Muhamad Husain, Siti Fatimah Husain (2018)
Satisfactory service behavior based on clients and takaful agencies perspective: a case study in Academy Etika Takaful Berhad. The objectives of this study are to identify the factors that effected unsatisfactory service behavior among takaful agents. Subsequently the second objective was to research how the issues were handled by Etika Family Takaful Berhad and lastly to identify the way of Etika Family Takaful Berhad to ensure that the issues was prevented from continuing to happen. This study will use questionnaire and interview methods such as quantitative and qualitative methods as information collection methods. The researcher selected the study location at the Academy Etiqa Takaful Berhad in Kuala Lumpur as the location of the study. Ultimately, these objectives had been reached at the end of the study and the result will provides as contribution to the company and public society in further management of satisfactory service behavior.